(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize recent evidence on the burden of male infertility, temporal changes in semen quality, and the association of modern lifestyle and environmental factors with male reproductive health. Methods: This practice-oriented narrative review searched PubMed and the official websites of WHO, EAU, and AUA/ASRM for the period 2016–2025; guideline webpages were cross-checked up to March 10, 2026. After reviewing titles, abstracts, and full texts according to predefined objectives, 10 key sources were selected for direct citation and qualitatively synthesized into three main thematic domains. Results: Current evidence indicates that male factors are involved in approximately half of infertility cases among couples. The burden of diagnosed male infertility appears to have increased over time, particularly in middle-income countries. Several meta-analyses have reported declining sperm concentration and total sperm count, although interpretation remains limited by interlaboratory variation, changes in assessment standards, and selection bias. Cigarette smoking, obesity or metabolic dysfunction, prolonged scrotal heat exposure, and endocrine-disrupting chemicals show the most consistent associations with adverse semen parameters and reproductive hormones. Conclusion: Male infertility is an important and partly modifiable reproductive health problem. A practical approach should combine standardized semen analysis, evaluation of reversible causes, and prioritized lifestyle intervention, with reassessment after about 3 months.